2014
DOI: 10.1371/journal.pone.0105864
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Mechanism behind the Costs Associated with Resistance to Bacillus thuringiensis in the Cabbage Looper, Trichoplusia ni

Abstract: Beneficial alleles that spread rapidly as an adaptation to a new environment are often associated with costs that reduce the fitness of the population in the original environment. Several species of insect pests have evolved resistance to Bacillus thuringiensis (Bt) toxins in the field, jeopardizing its future use. This has most commonly occurred through the alteration of insect midgut binding sites specific for Bt toxins. While fitness costs related to Bt resistance alleles have often been recorded, the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 67 publications
3
26
1
Order By: Relevance
“…These two p:c ratios are within the range found in T. ni host plants ( Morehouse and Rutowski, 2010). The optimal p:c ratio for the development of T. ni is approximately 1p:1c (Shikano and Cory, 2014b), and when given a choice between two suboptimal diets that are together complimentary, T. ni will compose a nutrient intake of 1.3p:1c (Shikano and Cory, 2014a). We modified the recipe from Shikano and Cory (2014a) by adding more wheat-germ oil (3.5% of total dry diet) as this reduced wing deformities in adults; an equivalent amount of cellulose was removed.…”
Section: Treatment Dietssupporting
confidence: 69%
“…These two p:c ratios are within the range found in T. ni host plants ( Morehouse and Rutowski, 2010). The optimal p:c ratio for the development of T. ni is approximately 1p:1c (Shikano and Cory, 2014b), and when given a choice between two suboptimal diets that are together complimentary, T. ni will compose a nutrient intake of 1.3p:1c (Shikano and Cory, 2014a). We modified the recipe from Shikano and Cory (2014a) by adding more wheat-germ oil (3.5% of total dry diet) as this reduced wing deformities in adults; an equivalent amount of cellulose was removed.…”
Section: Treatment Dietssupporting
confidence: 69%
“…They found that the resistant strain had better survival in the presence of Cry1Ac, but that diet P:C did not significantly affect survival for either strain. Shikano and Cory43 did find differences in the effect of diet P:C on Bt -related mortality for a susceptible and resistant strain of Trichoplusia ni . In their study, survival of the susceptible strain increased as diet P:C increased in the presence of B. thuringiensis , while the resistant strain had higher mortality on the most protein-biased diet.…”
Section: Discussionmentioning
confidence: 94%
“…Currently the effects of nutrition on insecticide susceptibility and resistance is poorly understood, particularly in agricultural systems where environmentally-mediated effects may have significant economic implications434445. Helicoverpa zea , known as the cotton bollworm or corn earworm, is a widespread New World lepidopteran pest targeted by Bt transgenic plants.…”
mentioning
confidence: 99%
“…Few studies have focused on the importance of host-plant quality prior to pathogen exposure, but phytochemicals and nutrients are known to alter levels of constitutive immunity and physical barriers to pathogens that prevent or reduce the establishment of infection. Dietary macronutrient content strongly influenced the resistance of T. ni larvae to Bacillus thuringiensis challenge (Shikano & Cory, 2014) and host plant species altered constitutive phenoloxidase activity, haemocyte numbers, host condition, and T. ni resistance to a baculovirus (Shikano et al, 2010). Phytochemical and nutritional effects on physical barriers include changes to the thickness of the peritrophic matrix (Plymale et al, 2008) and the rate of midgut cell sloughing (Hoover et al, 2000), which protect against infection by pathogens that need to be ingested, and the degree of melanisation of the cuticle (Lee et al, 2008) which protects against pathogens such as fungi that invade through the cuticle.…”
Section: Introductionmentioning
confidence: 99%